Performative Print: A Printing Anomaly in The Coblers Prophesie - Eastwood, Frances (Early Theatre)

(untitled) (McMaster University Library Press / Becker Associates, 2023)
Signature F2r of The Coblers Prophesie (1594) by Robert Wilson brings the reader to an abrupt halt – it contains a page-stopping stage direction in gargantuan type. This article examines whether the outsized print was a botched job by the printer Thomas Scarlet or an intentional ploy to engage the reader. The anomaly suggests that printers exercised agency in textual production and collaborated in the creative impact of printed material. Play-texts exist at the intersection of print and performance, and this case study poses larger questions about the complex relationship between the theatre and the printing house in early modern England.